Neurohumoral improvement and torsional dynamics in patients with heart failure after treatment with levosimendan. (1st June 2015) - Navarri, Romina; Lunghetti, Stefano; Cameli, Matteo; Mondillo, Sergio; Favilli, Roberto; Scarpini, Francesca; Puccetti, Luca
Abstract: Background: Levosimendan improves clinical and hemodynamic parameters exerting an anti-inflammatory and antiapoptotic effect in decompensated heart failure. The aim of this study was to evaluate the effects of levosimendan on LV torsion, plasma levels of NT-proBNP and on the balance between pro-inflammatory (TNF-α, IL-6) and anti-inflammatory cytokines (IL-10). Methods: We enrolled 24 patients (age 62 ± 7 years) with acute HF, NYHA class IV and severe LV dysfunction. All patients underwent transthoracic echocardiography using two-dimensional speckle tracking analysis to detect LV twist angle (LVTA), at baseline and 1 week after treatment with levosimendan infusion. Biochemical parameters (pro-BNP, IL-6, IL-10, TNF-α) were determined by enzyme-linked immunosorbent (ELISA). Results: After one week, we observed an improvement in LV function especially in LVTA (4.15 ± 2.54 vs 2.9 ± 2.1 p < 0.01), in LV ejection fraction (27.3 ± 8.04 vs 21.6 ± 6.8 p = 0.03) and also a significant reduction in BNP levels (1844 ± 560 vs 4713 ± 1050, p = 0.03). The multiple linear regression analysis showed a significant relation between a reduction of TNF α/IL-10 ratio (Δ > 20%) and BNP (Δ > 40%), LVEF (Δ > 10%) and LVTA (Δ > 20%) (O.R. 1.77, 95% C.I. 1.11–2.83; O.R. 1.49, 95% C.I. 1.08–2.67; O.R. 1.66, 95% C.I. 1.10–2.74, respectively, confirmed p, all < 0.01 by Hosmer–Lemeshov confirmation and the formal test for interaction). Conclusions: Levosimendan exerts a hemodynamic effect by improving EF and LV torsion in patients with acute HF in association with a positive effect on the balance between pro and anti-inflammatory cytokines.